Río y suburbio - Iván Portugués Mollá; Joan F. Mateu Bellés (Cuadernos de Geografía de la Universitat de València)
During the first postwar years the section of the Turia River in Valencia suffered obvious degradation. The settlement of shanty towns and the generalization of aggressive practices transformed the channel into an elongated slum, whose administration was quite beyond the capacities of the hydraulic and municipal authorities. The river flood of 1949 proved the vulnerability of the system and was the inflection point in favor of defensive works and the embellishment of the river in the most urban stretch.